Pengaruh Disiplin Kerja terhadap Kinerja Personel Polres Pamekasan yang Dimediasi oleh Promosi Jabatan - Chamariyah Chamariyah; Rico Budi Pratama; Subijanto Subijanto (Journal of Management and Creative Business, 2025)
Rico Budi Pratama, 2025. The Effect of Work Discipline on the Performance of Pamekasan Police Personnel Mediated by Position Promotion, Postgraduate Program, Wijaya Putra University. This type of research is explanatory (Explanatory Research) research that analyzes the relationships between one variable and another or how a variable affects another variable through hypothesis submission, using a quantitative approach, the research sample was 88 respondents. In this study the data will be processed using SEM-PLS data analysis. The objectives of this study are: 1) To determine and analyze the direct effect of work discipline on the performance of Polres personnel. 2) To determine and analyze the direct effect of work discipline on job promotion 3) To determine and analyze the direct effect of job promotion on personnel performance. 4) To determine and analyze the indirect effect of work discipline on personnel performance mediated by job promotion. The results showed that: 1) Work discipline has a direct and significant effect on personnel performance. 2) Work discipline has a direct and significant effect on job promotion. 3) Job promotion has a direct and significant effect on personnel performance. 4) Work discipline has an indirect and significant effect on personnel performance mediated by job promotion.